Tachinid flies (Diptera: Tachinidae) associated with crop pests in northern Cameroon, with the description of a new species of Carcelia Robineau-Desvoidy - (:unkn) unknown (My University, 2019)
Agroecological research was carried out in northern Cameroon from 2008 to 2014 to develop a strategy aiming to encourage the action of natural enemies against lepidopteran pests in cotton crops and in surrounding landscapes. Tachinidae is one of the most diverse families of Diptera in the Afrotropics and represents an important group of endoparasitoids, although their role as biocontrol agents in crops is still poorly understood in Africa. Tachinid flies were collected and reared from lepidopteran caterpillars found in agricultural settings, with a particular attention to the cotton bollworm, a major pest in the region, and from the coreid Anoplocnemis curvipes. A total of 127 specimens of tachinids belonging to 21 species/morphospecies have been recorded, including a new species of Carcelia, Carcelia ethillamima Cerretti, n. sp. and six new records for Cameroon, Campylocheta risbeci, Goniophthalmus halli, Pseudogonia rufifrons, Carcelia peraequalis, Exorista xanthaspis, and Paraclara magnifica. The study improves our knowledge of these parasitoids in Central Africa and our understanding of host–parasitoid relationships in this dipteran family.
Keywords: African Research